Acidic Microenvironment Aggravates the Severity of Hepatic Ischemia/Reperfusion Injury by Modulating M1-Polarization Through Regulating PPAR-γ Signal - Ding, Wei; Duan, Yunfei; Qu, Zhen; Feng, Jiawei; Zhang, Rongsheng; Li, Xiaodong; Sun, Donglin; Zhang, Xiaoying; Lu, Yunjie (Frontiers in Immunology, 2021)
Hepatic injury induced by ischemia and reperfusion (HIRI) is a major clinical problem after liver resection or transplantation. The polarization of macrophages plays an important role in regulating the severity of hepatic ischemia/reperfusion injury. Recent evidence had indicated that the ischemia induces an acidic microenvironment by causing increased anaerobic glycolysis and accumulation of lactic acid. We hypothesize that the acidic microenvironment might cause the imbalance of intrahepatic immunity which aggravated HIRI. The hepatic ischemia/reperfusion injury model was established to investigate the effect of the acidic microenvironment to liver injury. Liposomes were used to deplete macrophages in vivo. Macrophages were cultured under low pH conditions to analyze the polarization of macrophages in vitro. Activation of the PPAR-γ signal was determined by Western Blot. PPAR-γ agonist GW1929 was administrated to functionally test the role of PPAR-γ in regulating macrophage-mediated effects in the acidic microenvironment during HIRI. We demonstrate that acidic microenvironment aggravated HIRI while NaHCO3 reduced liver injury through neutralizing the acid, besides, liposome abolished the protective ability of NaHCO3 through depleting the macrophages. In vivo and vitro experiment showed that acidic microenvironment markedly promoted M1 polarization but inhibited M2 polarization of macrophage. Furthermore, the mechanistic study proved that the PPAR-γ signal was suppressed during the polarization of macrophages under pH=6.5 culture media. The addition of PPAR-γ agonist GW1929 inhibited M1 polarization under acidic environment and reduced HIRI. Our results indicate that acidic microenvironment is a key regulator in HIRI which promoted M1 polarization of macrophages through regulating PPAR-γ. Conversely, PPAR-γ inhibition reduced liver injury, which provides a novel therapeutic concept to prevent HIRI.